Length-Weight Relationship and Fulton’s Condition Factor of the Nile Tilapia (Oreochromis niloticus L., 1758) in Lake Chamo, Ethiopia - Shija, Buchale Shishitu (Journal of Agriculture and Environmental Sciences, 2020)
The objectives of the study were to determine the length-weight relationship and Fulton’s condition factor of O. niloticus in Lake Chamo, Southern region of Ethiopia. Data for total length (TL), total weight (TW) and sex were collected from 5,778 fish samples (3577 females and 2201 males) for nine months (February to October 2018) from commercial fishery of Lake Chamo. The collected data were summarized using descriptive statistics (graphs and tables) and analyzed with the application of Microsoft Excel 2010 and SPSS Software. The length-weight relationship was calculated using power function and obtained as TW = 0.0112*TL3.14, (R2 = 0.96), TW = 0.0102*TL3.19, (R2 = 0.98) and TW = 0.0102*TL3.18, (R2 = 0.97) for male, female and pooled sexes, respectively. The b value in this study was greater than the cubic (b > 3) value and indicates that both males and females of O. niloticus in Lake Chamo followed positive allometric growth pattern. The average Fulton’s condition factor (K) value for male, female and combined sex was 1.78, 1.96 and 1.85, respectively. The one-way ANOVA (P > 0.05) revealed that Fulton’s condition factor by month’s interaction was insignificant. But the condition factor of both sexes in Lake Chamo was significantly different (ANOVA, p < 0.05). There was highly significant differences between sexes interaction (t-test, P = 0.000) which indicates the presence of temporal variation between both sexes in Fulton’s condition factor. All the values of Fulton’s condition factors of male, female and combined sex of O. niloticus were above 1.6 and indicates that O. niloticus of Lake Chamo was in a very good condition throughout the study period. Future studies including other species of fish are also recommended